Postdural Puncture Headache: Incidence and Risk Factors in Children Following Intrathecal Chemotherapy - BANI HASHEM, Abdulah; HEYDARIAN, Farhad; GHARAVI, Mohammad; KHOSHNOD, Mohsen (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Bani hashem A, Heydarian F, Gharavi M, Khoshnod M. Postdural Puncture Headache: Incidence and Risk Factors in Children FollowingIntrathecal Chemotherapy. Iranian Journal of Child Neurology 2012;6(1):19-22. Objective To evaluate the incidence and risk factors of development of postdural puncture headache in children who had intrathecal chemotherapy injection. Materials & Methods Two-hundred eighty patients (mean age, 7.23±3.92 years) who had intrathecal chemotherapy injection were studied prospectively during 2008-2009 in the pediatric ward of Dr. Sheikh hospital in Mashhad. Patients who had lumbar puncture for their chemotherapy drug injections were assessed daily for four days to detect postdural puncture headache. Results There were 172 (61, 4%) male patients and the remainder were female. Postdural puncture headache was detected in 41 patients (14.6%). The body mass index did not show any significant difference between the two groups. Lumbar puncture (LP) attempts had a significant association with postdural puncture headache. The size and shape of the needle did not have a significant association with postdural puncture headache. Conclusion LP attempts have a significant relationship with postdural puncture headache. References: 1. Bolder PM. Postlumbar puncture headache in pediatriconcology patients. Anesthesiology. 1986;65:696-8. 2. Ozyalcin NS, Menda F. Regional anesthesia and analgesiaapplications in children and infants – II. Agri 2004;16:29-34, 37-42. 3. Oilver A. Dural punctures in children: what should wedo? Paediatr Anaesth. 2002;12:473-7. 4. Kokki H, Hendolin H, Turunen M. Postdural punctureheadache and transient neurologic symptoms in childrenafter spinal anaesthesia using cutting and pencil pointpaediatric spinal needles. Acta Anaesthesiol Scand1998;42:1076-82. 5. Lowery S, Oliver A. Incidence of postdural punctureheadache backache following diagnostic therapeuticlumbar puncture using a 22G cutting spinal needle, andafter introduction of a 25G pencil point spinal needle.Pediatr Anesth. 2008;18:230-4 6. Apiliogulari S, Duman A, Gok F, Akilliouglu L.Spinal needle design and size affect the incidence ofposdural puncture headache in children. Pediatr Anesth2010;20:177-82. 7. Kokki H, Heikkinen M, Turunen M. Needle design doesnot affect the success rate of spinal anaesthesia or theincidence of postpuncture complications in children. ActaAnaesthesiol Scand 2000;44:210-3. 8. Hammond ER, Wang Z, Bhulani N, McArthur JC, LevyM. Needle Type and the risk of post-lumber punctureheadache in the outpatient neurology. Clin J Neurol Sci;306(2011):24-8. 9. Lybecker H, Djernes M, Schimidt JF. Postdural punctureheadache (PDPH): onset, duration, severity and associatedsymptoms. An analysis of 75 consecutive patients withPDPH. Acta Anaesthesiol Scand 1995;39:605-12. 10. Seeberger MD, Kaufman M, Staender S, Schneider M,Scheidegger D. Repeated dural punctures increase theincidence of postdural puncture headache. Anesth Analg1996;82:302-5. 11. Thomas SR, Jamison DR, Muir KW. Randomizedcontrolled trial of atraumatic versus standard needles fordiagnostic lumbar puncture. BMJ 2000;3210:986-90. 12. Strupp M, Schueler O, Straube A. Atroumatic Sprotteneedle reduces the incidence of post-lumbar punctureheadaches. Neurology 2001;57:2310-2. 13. Kleyweg RP, Hetzberger LI, Carbat PA. Significantreduction in post-lumber puncture headache using an atraumatic needle. Cephalalgia 1998;18:635-7. 14. Lybecker H, Moller JT, May O. Incidence and predictionof postural puncture headache. A prospective study of1021 spinal Anesthesias. Anesth Analg 1990;70:389-94.15. Helper S, Preston R. Postdural puncture headache andspinal needle design. Meta analyses. Anesthesiology1994:81:1376-83. 16. Parker RK, White PF. A microscopic analysis of cutbevelversus pencil-point spinal needles. Anesth Analg1997;85:1101-4. 17. Reina MA, de leon Casasola OA, Lopez A. An in vitrostudy of dural lesions produced by 25-gauge Quinckeand Whitacre needles evaluated by scanning electronmicroscopy. Reg Anesth Pain Med 2000;393-402.